The Effect Of Transfer Pricing And Political Connections On Tax Avoidance With Profitability As A Moderating Variable - Caroline Yoshe Kolondam; Intan Kurnia Permatasari (Eduvest - Journal of Universal Studies, 2024)
This study aims to analyze the effect of transfer pricing and political connections on tax avoidance with profitability as a moderating variable. The research method used is quantitative and data analysis techniques using multiple linear regression and MRA. This study uses a sample of multinational manufacturing sector companies listed on the Indonesia Stock Exchange in 2018-2022. The total sample used was 66 companies with a research period of 5 years, namely 2018-2022, so that 330 samples were obtained. The results of this study indicate that the transfer pricing variable has a positive effect on tax avoidance and the profitability variable can moderated relationship between transfer pricing and tax avoidance, while political connections do not affect tax avoidance even with profitability moderation.